Pengaruh Belanja Online Terhadap Perilaku Konsumtif pada Mahasiswa di Masa Pandemi Covid-19 - Dela Septiansari; Trisni Handayani (Jurnal EMT KITA, 2021)
At the time of the covid-19 pandemic, as it is today, it changed the consumption pattern of the community, especially for students. The consumption behavior of students tends to increase due to several influencing factors, one of which is a glamorous lifestyle. This study aims to determine the effect of online shopping on the consumptive behavior of students of Economics Education FKIP UHAMKA. The population in this study were students of Economics Education FKIP UHAMKA Academic Year 2020/2021, totaling 307 students with a research sample of 174 students. This study uses a quantitative approach. The technique of collecting samples using simple random sampling technique. The process of collecting data in this study used questionnaires via google form. Then the results of the information were analyzed by correlation and regression analysis. The results showed that there was a significant correlation and influence between online shopping on consumptive behavior, which was 25.8%. This means that online shopping has a positive and significant effect on consumptive behavior among students in using online shopping applications. In addition, student consumptive behavior cannot be avoided without the awareness to be wise in using online shopping applications. Furthermore, the average student does online shopping without considering time and needs.